Property law : rules, policies, and practices - Singer, Joseph William, 1954-; Berger, Bethany R.; Davidson, Nestor M.; Peñalver, Eduardo M., 1973- (Frederick : Aspen Publishing, 2022)
"Casebook on Property law for law students; includes notes, questions, and problems"--
Trespass : the right to exclude and rights of access -- Competing justifications for property rights -- What can be owned? -- Adverse possession -- Nuisance : resolving conflicts between free use and quiet enjoyment -- Land use and natural resources regulation -- Servitudes : rules governing contractual restrictions on land use -- Concurrent, family, and entity property -- Present estates and future interests -- Leaseholds -- Real estate transactions -- Fair housing law -- Takings law.
Includes bibliographical references and index.
SOL
Trim Education
Keywords: Property -- United States; Property -- United States. -- Cases; Law